Genomic sequencing and evolutionary analysis of bovine kobuvirus in Yunnan Province, China - Guojun Wang; Qiuhui Deng; Peiying Zhu; Veerasak Punyapornwithaya; Xuseng Shi; Yan Liu; Xinhui Duan; Zailei Li; Wengui Li (BMC Veterinary Research)
Abstract Background Bovine Kobuvirus (BKV) is an emerging pathogen associated with diarrhea in cattle. Limited reports on its prevalence and genetic characteristics are available. To determine the epidemiology and genetic evolution of BKV strains circulating in Yunnan Province, China, 204 diarrheal samples were collected from cattle farms across five regions for screening for BKV infection. Results RT-PCR analysis identified 40 BKV-positive samples, yielding an infection rate of 19.6%. Positive samples were inoculated into Vero cells for continuous passage, followed by molecular biology, immunofluorescence, and electron microscopy identification. Two BKV strains, BKV YN-1 2023 and YN-2 2023, were isolated. Whole-genome sequencing revealed genome lengths of 8289 bp and 8291 bp (GenBank No. PV410179 and PV410180), respectively. Phylogenetic analysis demonstrated that both strains belong to genotype B, the dominant genotype circulating in China, and are closely related to the previously reported Chinese strain BKV 13/2021. The genetic similarity of two BKV isolates was analyzed. Genome-wide nucleotide identities ranged from 39.9 to 93.9%, with the highest similarity to BKV13 2021 CHN. ORF analysis showed nucleotide and amino acid similarities of 48.7–93.9% and 29.3–98.5%, respectively. Compared to the BKV13 2021 CHN, both isolates exhibited high conservation in VP0, VP3, and nonstructural proteins (97.8–100%), while the L protein had the lowest similarity (94.7–95.2%). The 5′ UTR showed lower conservation than the 3′ UTR, suggesting regulatory variations. Conclusions These findings reveal that the circulating BKV strains in Yunnan belong to the globally prevalent genotype B and are widely distributed. This study provides valuable insights into the molecular epidemiology, genetic diversity and evolutionary dynamics of BKV, offering an important reference for developing diagnostics, vaccines and further studies on its pathogenesis.